Next Generation Computer Animation Techniques : Third International Workshop, AniNex 2017, Bournemouth, UK, June 22-23, 2017, Revised Selected Papers /: Third International Workshop, AniNex 2017, Bournemouth, UK, June 22-23, 2017, Revised Selected Papers. (2017) - Unknown
No abstract available